2019
DOI: 10.1111/evj.13182
|View full text |Cite
|
Sign up to set email alerts
|

Warmblood fragile foal syndrome type 1 mutation (PLOD1 c.2032G>A) is not associated with catastrophic breakdown and has a low allele frequency in the Thoroughbred breed

Abstract: Summary Background Catastrophic fractures are among the most common cause of fatalities in racehorses. Several factors, including genetics, likely contribute to increased risk for fatal injuries. A variant in the procollagen‐lysine, 2‐oxoglutarate 5‐dioxygenase1 gene (PLOD1 c.2032G>A) was shown to cause Warmblood fragile foal syndrome type 1 (WFFS), a fatal recessive defect of the connective tissue. Screening of multiple horse breeds identified the presence of the WFFS allele in the Thoroughbred. PLOD1 is invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…The occurrence of WFFS carriers in Thoroughbreds has been shown previously to be 2.4% in Bellone et al, 2019 [30], but all 146 Thoroughbreds from Poland genotyped in this study were homozygous for the reference allele (PLOD1:c.2032G).…”
Section: Distribution Of the Wffs Allelesupporting
confidence: 39%
See 2 more Smart Citations
“…The occurrence of WFFS carriers in Thoroughbreds has been shown previously to be 2.4% in Bellone et al, 2019 [30], but all 146 Thoroughbreds from Poland genotyped in this study were homozygous for the reference allele (PLOD1:c.2032G).…”
Section: Distribution Of the Wffs Allelesupporting
confidence: 39%
“…The collection includes Thoroughbreds, warmblood horse breeds, Quarter Horses, breeds derived from warmbloods, and breeds in which warmbloods are allowable crosses. The sample set was also supplemented by a large number of Arabians (302), a selection of baroque horses, such as Friesians and Lippizans, and draft and pony breeds ( The 716 Thoroughbred horses included in this study were used in Bellone et al, 2019 [30] and were included here for completeness of the dataset.…”
Section: Sample Description Population Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Thoroughbred contributed to about 34.8% to the genes of the Hanoverian population (reference population 1980‐2000) 41 . Furthermore, a genotyping study of 716 Thoroughbred racehorses for WFFST1 variant confirmed that the mutant WFFST1 allele is present in the Thoroughbred population with a relatively low frequency of 1.2% 25 . The transmission of WFFST1 mutant allele from a Thoroughbred horse and the wide distribution in Warmblood horses might therefore be explained by the fact that Thoroughbred stallions which influence Warmblood breeding are no longer used for breeding in the Thoroughbred population.…”
Section: Discussionmentioning
confidence: 89%
“…Genetic testing for FFS has been commercially available since 2013 2 . Initially, it was assumed that FFS was only found in Warmbloods and related breeds, 2 but recent studies have identified FFS‐positive Thoroughbreds 3 . The aim of this work was to make unbiased observations of the frequency of FFS across horse breeds (Figure 1).…”
Section: Figurementioning
confidence: 99%